2002
DOI: 10.1038/ng1051
|View full text |Cite
|
Sign up to set email alerts
|

Long-range chromatin regulatory interactions in vivo

Abstract: Communication between distal chromosomal elements is essential for control of many nuclear processes. For example, genes in higher eukaryotes often require distant enhancer sequences for high-level expression. The mechanisms proposed for long-range enhancer action fall into two basic categories. Non-contact models propose that enhancers act at a distance to create a favorable environment for gene transcription, or act as entry sites or nucleation points for factors that ultimately communicate with the gene. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
458
1
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(482 citation statements)
references
References 23 publications
17
458
1
6
Order By: Relevance
“…The role of cis-acting elements in the regulation of γ-globin gene expression was explored through RNA-TRAP and chromosome conformation capture (3-C) experiments in transgenic mice carrying the entire or selected regions of the human β-globin locus. RNA TRAP experiments provided evidence that HS2 is in close proximity to the actively transcribed β-globin gene, in agreement with genetic data suggesting that HS2 is the most prominent enhancer element in the β-globin LCR [4]. In this context, particularly significant were the 3-C experiments carried out in transgenic mice carrying the entire human β-globin locus: These mice show a switch in the association of HS2 and HS3 sites in the βLCR from contacts with embryonic and fetal genes in yolk sac cells to contacts with the adult human β-globin in adult-type erythroid cells [5].…”
Section: Regulation Of γ-Globin Gene Expressionsupporting
confidence: 82%
“…The role of cis-acting elements in the regulation of γ-globin gene expression was explored through RNA-TRAP and chromosome conformation capture (3-C) experiments in transgenic mice carrying the entire or selected regions of the human β-globin locus. RNA TRAP experiments provided evidence that HS2 is in close proximity to the actively transcribed β-globin gene, in agreement with genetic data suggesting that HS2 is the most prominent enhancer element in the β-globin LCR [4]. In this context, particularly significant were the 3-C experiments carried out in transgenic mice carrying the entire human β-globin locus: These mice show a switch in the association of HS2 and HS3 sites in the βLCR from contacts with embryonic and fetal genes in yolk sac cells to contacts with the adult human β-globin in adult-type erythroid cells [5].…”
Section: Regulation Of γ-Globin Gene Expressionsupporting
confidence: 82%
“…Though there are a host of interesting examples of transcriptional regulation that involve DNA looping, we focus almost exclusively on the dissection of the role of looping in 85 Repression and activation 210 Gal repressor 85 Repression 115 Deo repressor 85 Repression 270, 599, 869 Nag repressor 86 Repression 93 NtrC 87 Activation 110-140 l repressor 84,88 Repression and activation $2400 XylR 89 Activation $150 PapI 87,90 Activation $100 -globin locus 91,92 Activation 40,000-60,000 RXR 93 Activation 30-500 SpGCF1 94 Activation, domain intercommunication 50-2500 HSTF 95 Activation 23 p53 96 Repression and activation 50-3000 Sp1 [97][98][99] Activation $1,800 c-Myb and C/EBP 100 Activation $80…”
Section: Tightly Bent Dna In Transcriptional Regulationmentioning
confidence: 99%
“…www.genome.org RNA-TRAP showed that the expressed globin gene interacted most strongly with HS2 (Carter et al 2002).…”
Section: Genome Research 1305mentioning
confidence: 99%
“…This locus was selected because several looping interactions have previously been detected by 3C as well as by a second method, RNA-TRAP (Carter et al 2002;Tolhuis et al 2002), and therefore detection of these looping interactions using 5C can be used to validate the new method.…”
Section: Chromatin Looping In the Human ␤-Globin Locusmentioning
confidence: 99%